Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 147467 by mathmax by abdo last updated on 21/Jul/21

f(x)=x^n  e^(−x)   1) calculate f^((n)) (0) and f^((n)) (1)  2)developp f at integr serie  3) calculate ∫_0 ^1  f(x)dx

f(x)=xnex1)calculatef(n)(0)andf(n)(1)2)developpfatintegrserie3)calculate01f(x)dx

Answered by mathmax by abdo last updated on 22/Jul/21

1)leibniz give f^((p)) (x)=Σ_(k=0) ^p C_p ^k  (x^n )^((k)) (e^(−x) )^((p−k))  ⇒  =Σ_(k=0) ^p  C_p ^k (−1)^(p−k)  e^(−x) (x^n )^((k))   if k>n  ⇒(x^n )^((k))  =0  if k≤n     ⇒(x^n )^((k))  =n(n−1)...(n−k+1)x^(n−k)   =((n!)/((n−k)!))x^(n−k)   we have  f^((n)) (x)=Σ_(k=0) ^n  C_n ^k  (−1)^(n−k)  e^(−x) ×((n!)/((n−k)!))x^(n−k)   =Σ_(k=0) ^(n−1) (...)x^(n−k) +e^(−x) n! ⇒f^((n)) (0)=n!

1)leibnizgivef(p)(x)=k=0pCpk(xn)(k)(ex)(pk)=k=0pCpk(1)pkex(xn)(k)ifk>n(xn)(k)=0ifkn(xn)(k)=n(n1)...(nk+1)xnk=n!(nk)!xnkwehavef(n)(x)=k=0nCnk(1)nkex×n!(nk)!xnk=k=0n1(...)xnk+exn!f(n)(0)=n!

Commented by mathmax by abdo last updated on 22/Jul/21

f^((n)) (1)=e^(−1)  Σ_(k=0) ^n  (−1)^(n−k)  ((n!)/(k!(n−k)!))×((n!)/((n−k)!))  =(−1)^n e^(−1)  Σ_(k=0) ^n  (((−1)^k )/(k!))×(((n!)^2 )/(((n−k)!)^2 ))

f(n)(1)=e1k=0n(1)nkn!k!(nk)!×n!(nk)!=(1)ne1k=0n(1)kk!×(n!)2((nk)!)2

Answered by mathmax by abdo last updated on 22/Jul/21

2) we have f(x)=x^n  e^(−x)  =x^n  Σ_(p=0) ^∞  (((−x)^p )/(p!))  =Σ_(p=0) ^∞  (((−1)^p )/(p!))x^(n+p)  =_(n+p=k)   Σ_(k=n) ^∞  (((−1)^(k−n) )/((k−n)!)) x^k

2)wehavef(x)=xnex=xnp=0(x)pp!=p=0(1)pp!xn+p=n+p=kk=n(1)kn(kn)!xk

Answered by mathmax by abdo last updated on 22/Jul/21

3) A_n =∫_0 ^1  x^n  e^(−x)  dx   by parts we get  A_n =[(x^(n+1) /(n+1))e^(−x) ]_0 ^1 +∫_0 ^1  (x^(n+1) /(n+1))e^(−x)  dx=(e^(−1) /(n+1)) +(1/(n+1)) A_(n+1)  ⇒  (n+1)A_n =(1/e) +A_(n+1)  ⇒A_(n+1) =(n+1)A_n −(1/e) ⇒  A_n =nA_(n−1) −(1/e)  let u_n =(A_n /(n!)) ⇒  u_(n+1) =(A_(n+1) /((n+1)!))=(((n+1)A_n −(1/e))/((n+1)!))=(A_n /(n!))−(1/(e(n+1)!))  =u_n −(1/(e(n+1)!)) ⇒u_(n+1) −u_n =−(1/(e(n+1)!)) ⇒  Σ_(k=0) ^n  (u_(k+1) −u_k )=−(1/e)Σ_(k=0) ^n  (1/((k+1)!)) ⇒  u_n −u_0 =−(1/e)Σ_(k=1) ^(n+1)  (1/(k!)) ⇒u_n =u_o −(1/e)Σ_(k=1) ^(n+1)  (1/(k!))  u_o =A_0 =∫_0 ^1  e^(−x)  dx=[−e^(−x) ]_0 ^1  =1−(1/e) ⇒  u_n =1−(1/e)Σ_(k=0) ^(n+1 )  (1/(k!))  A_n =n!u_n =n!(1−(1/e)Σ_(k=0) ^(n+1)  (1/(k!)))

3)An=01xnexdxbypartswegetAn=[xn+1n+1ex]01+01xn+1n+1exdx=e1n+1+1n+1An+1(n+1)An=1e+An+1An+1=(n+1)An1eAn=nAn11eletun=Ann!un+1=An+1(n+1)!=(n+1)An1e(n+1)!=Ann!1e(n+1)!=un1e(n+1)!un+1un=1e(n+1)!k=0n(uk+1uk)=1ek=0n1(k+1)!unu0=1ek=1n+11k!un=uo1ek=1n+11k!uo=A0=01exdx=[ex]01=11eun=11ek=0n+11k!An=n!un=n!(11ek=0n+11k!)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com